Processo de diferenciação gonodal em Pseudoplatystoma fasciatum e tentativa de feminilização com 17β-estradiol - Valentin, Fernanda Nogueira [UNESP] (2013)
Pseudoplatystoma fasciatum is an important species, with unspined meat, delicate flavor and firm texture. Females of this species reach larger sizes and have better growth rates than males. The objective of this study was to describe the gonad development and differentiation of P. fasciatum and evaluate the potential feminization effect of the 17β - estradiol hormone. For development and gonadal differentiation description, P. fasciatum juveniles were obtained through the hormonal induction of various breeders maintained in different reproductive stations and fish farms of inducted reproduction (Centro de Aquicultura Unesp “CAUNESP”, Andrade and Mar&Terra piscicultures); for the hormonal treatment juveniles were obtained and maintained in Mar&Terra pisciculture. Samples for development and gonadal differentiation were performed on pre-set points starting from 39 days post-fertilization (dpf) until complete 240 dpf. For the hormonal treatment juveniles (39 dpf) were fed daily to satiation with artificial food incorporated with 17β-estradiol. We used a control group and three treated groups (50, 100, 150mg/kg of commercial extruded feed containing 40% crude protein). Sampling started at 39 (dpf) and periodically at the following times 45, 57, 70 and 100 dpf. At 39 dpf gonads were undifferentiated observed as simple structures, located ventrally to intestine and dorsally to kidney. From 39 to 45 dpf we observed the first histological clues of female and male gonad differentiation. At 60-70 dpf the external and internal differences of male and female gonads enabled the morphological identification of ovaries and testes precursors, however, both the male and the female gonad consisted mainly of somatic cells and rare germ cells of the undifferentiated type, referred as oogonia for female gonads and spermatogonia for male gonads. From 100 to 113 dpf, gonads from both sexes increased in size ...